Acoustic recognition of predators by mantled howler monkeys (Alouatta palliata): A playback experiment with naïve and experienced subjects - Sánchez-Vidal, Rafael Omar; Rangel-Negrín, Ariadna; Briseño-Jaramillo, Margarita; Sosa-López, J Roberto; Dias, Pedro A D (American journal of biological anthropology, 2024)
When the production of antipredator behaviors is costly, prey is expected to stop displaying such behaviors and lose the ability to recognize extirpated predators. However, the loss or maintenance of predator recognition abilities is conditional on the eco-evolutionary context of prey. Here, we examined the behavioral responses of naïve and experienced mantled howler monkeys (Alouatta palliata) to simulated acoustic cues from natural predators. We studied experienced individuals in the Uxpanapa Valley and naïve individuals in Los Tuxtlas (Veracruz, México). Jaguars (Panthera onca) and harpy eagles (Harpia harpyja), the main predators of howler monkeys, are extant in the Uxpanapa Valley but have been extirpated in Los Tuxtlas for approximately 70 and 45 years, respectively. We exposed six naïve and six experienced groups to playbacks of acoustic stimuli from the two predators and a non-predator control species (plain chachalacas, Ortalis vetula), and recorded the latency, frequency, and duration of antipredation behaviors (n = 127 trials). In contrast with experienced mantled howler monkeys, naïve subjects did not respond to trials from harpy eagles. However, response patterns were generally similar between naïve and experienced individuals when exposed to jaguar stimuli. Our findings suggest that naïve mantled howler monkeys do not recognize harpy eagle calls, but they respond to jaguar calls in a manner consistent with experienced individuals. These results illustrate how different mechanisms for the recognition of extirpated predators operate within a single species according to evolutionary and ecological experience.